Breaking the city: Militarization and segregation in Rio de Janeiro. (May 2016) - Fahlberg, Anjuli; Vicino, Thomas J.
Abstract: Emerging from the global city literature of the 1980s and 1990s, a vast scholarship has developed that embraces the 'dual city' concept as a useful analytical tool for explaining how global transformations produce polarization within cities. However, less is known about how local policies shape uneven patterns of development. Through an examination of Rio de Janeiro's Favela Pacification Program, we argue that state-level public policies play a significant role in institutionalizing duality. The recent military occupation of the slums in Rio de Janeiro demonstrates how the historically and politically contextualized public policy of confrontation has exacerbated tensions between the city's elites and poor residents along a number of social, economic, and political dimensions. Local policymakers can influence the impact of globalization on social polarization by considering the effects of public policies on spatial justice.